Difference in First Aid Activity During Mass Casualty Training Based on Having Taken an Educational Course. (20th November 2017) - Yanagawa, Youichi; Omori, Kazuhiko; Ishikawa, Kouhei; Takeuchi, Ikuto; Jitsuiki, Kei; Yoshizawa, Toshihiko; Sato, Jun; Matsumoto, Hideyuki; Tsuchiya, Masaru; Osaka, Hiromichi
ABSTRACT: Background: The Japanese Association for Disaster Medicine developed a mass casualty life support (MCLS) course to improve cooperation among medical practitioners during a disaster, which is essential for reducing the rates of preventable disaster death. We investigated whether there was difference in first aid activity among members of the ambulance service during mass casualty training based on having taken the MCLS course. Methods: Mass casualty training was held at the fire department of Numazu City. Twenty-one ambulance service parties participated in this training. They first evaluated the mass casualty situation, performed the appropriate services at the scene during the initial period, and then provided START triage for mock wounded patients. Throughout the training, 5 examiners evaluated their performance. Results: Regarding the difference in first aid activity based on MCLS course attendance among the ambulance service members, the cooperative management (scored on a scale of 1 to 5) among the members who had taken the MCLS course was significantly better than that among those who had not taken the course (median [interquartile range]: 5 [0.5] vs. 4 [1.75], P <0.05). Conclusion: Attending an MCLS course may help to improve outcomes in the face of an actual mass casualty incident. ( Disaster Med Public Health Preparedness . 2018;12:437–440)